Alternol triggers immunogenic cell death via reactive oxygen species generation. (1st January 2021) - Li, Changlin; Zhang, Ying; Yan, Siyuan; Zhang, Guoan; Wei, Wei; Qi, Zhi; Li, Benyi
ABSTRACT: Alternol is a naturally occurring compound that exerts antitumor activity in several cancers. However, whether Alternol induces antitumor immune response remains unknown. In this study, we investigated whether Alternol induced immunogenic cell death (ICD) in prostate cancer cells. Alternol triggered ICD in prostate cancer cells, as evidenced by the release of damage-associated molecular patterns (DAMPs) (i.e., calreticulin, CALR; high mobility group protein B1, HMGB1; and adenosine triphosphate, ATP) and pro-inflammatory cytokine (i.e., interleukin [IL]-1α, IL-1β, IL-6, and IL-8) expression. Alternol facilitated tumor-associated antigen uptake and cross-presentation, CD8 + T-cell priming, and T-cell infiltration in tumor-draining lymph nodes (LNs) and tumors. The presence of Alternol fostered antitumor immune response in vivo, resulting in delayed tumor growth and prolonged survival. Moreover, inhibition of reactive oxygen species (ROS) generation blocked Alternol-induced upregulation of pre-inflammation cytokines, endoplasmic reticulum (ER) stress, and consequent antitumor immune response. Overall, our data indicate that Alternol triggers ICD in prostate cancer cells, which is mediated by ROS generation.